Applying scientific reasoning to the field of marketing make better decisions - Grapentine, Terry. (2012 digital library., 2012)
Marketing decisions often misfire when driven more by beliefs than by knowledge. This book guides readers on how to differentiate between the two and to think more clearly and correctly when making those decisions, thereby increasing organizational success. The book is based on the fields of epistemology-- the study of how knowledge is created--and the philosophy of science--the study of what it means for a science to be called a science. The motivation behind the book is quite simple: Given that science is so successful, why shouldn't marketers borrow thinking and reasoning skills from science and apply them to marketing? Indeed, why not? Section 1 lays the groundwork for learning how to apply scientific reasoning to the field of marketing. It covers some basic and important definitions ("What is a belief?" "What is knowledge?"), identifies barriers to scientific reasoning, and gives an example from The Dow Chemical Company about how this manufacturer uses critical thinking and reasoning skills to make more effective marketing and business decisions. Section 2 presents the necessary "thinking tools" you will need to apply scientific reasoning to solving your marketing problems. It introduces topics relating to attributes versus constructs, the meaning of causation, the relationship between coherence and justified beliefs, the importance of logic to sound reasoning, and the avoidance of logical fallacies in making sound recommendations. The book's final section focuses on the role that theory development plays in helping marketers transform mere "beliefs" into "knowledge." Additionally, there is a separate chapter on brainstorming that presents ideas on how marketers can use their brain power to create potentially useful insights into factors influencing customer behavior. The book concludes by giving readers direction to further improve their ability to apply scientific reasoning to solve marketing problems.